2021
DOI: 10.3390/cancers13102362
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aneurysmal Bone Cyst and Its Recent Treatment Options: A Comparative Review of 74 Cases

Abstract: (1) Background: An aneurysmal bone cyst (ABC) is a benign, locally aggressive tumor. Different treatment modalities are described in the literature i.e., en bloc resection, intralesional curettage and percutaneous sclerotherapy. (2) Methods: This single-center study is a review of 74 patients with primary ABCs who underwent a surgical treatment or polidocanol instillation. Cyst volume measurements using MRI and conventional radiographs are compared. (3) Results: The mean pre-interventional MRI-based cyst volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
2
21
0
3
Order By: Relevance
“…This latter group also included larger lesions and lesions in more challenging locations, such as the spine, with a higher rate of complications. The results of the study [62] were similar to the study by Varshney et al [55], suggesting that percutaneous sclerotherapy and intralesional curettage were at least equally efficient in the treatment of ABC. Both Bavan et al [60] and Deventer et al [62] concluded that prospective, multicenter, randomized control studies with standardized protocols on interventions for the treatment of ABC were needed to draw a solid conclusion.…”
Section: Treatmentsupporting
confidence: 84%
See 3 more Smart Citations
“…This latter group also included larger lesions and lesions in more challenging locations, such as the spine, with a higher rate of complications. The results of the study [62] were similar to the study by Varshney et al [55], suggesting that percutaneous sclerotherapy and intralesional curettage were at least equally efficient in the treatment of ABC. Both Bavan et al [60] and Deventer et al [62] concluded that prospective, multicenter, randomized control studies with standardized protocols on interventions for the treatment of ABC were needed to draw a solid conclusion.…”
Section: Treatmentsupporting
confidence: 84%
“…The results of the study [62] were similar to the study by Varshney et al [55], suggesting that percutaneous sclerotherapy and intralesional curettage were at least equally efficient in the treatment of ABC. Both Bavan et al [60] and Deventer et al [62] concluded that prospective, multicenter, randomized control studies with standardized protocols on interventions for the treatment of ABC were needed to draw a solid conclusion. There are multiple studies advocating for sclerotherapy of ABC in spinal locations using various sclerosing agents [63][64][65][66].…”
Section: Treatmentsupporting
confidence: 84%
See 2 more Smart Citations
“…In a recent study, Deventer et al reported that out of 32 ABC patients treated with polidocanol sclerotherapy, 90.6% of patients had the persistent disease and 34.5% of patients further required treatment [ 30 ]. We feel the probable reason for these less satisfactory results is a radiological evaluation with an MRI scan.…”
Section: Discussionmentioning
confidence: 99%